Analisis Model Altman Z-Score, Springate, dan Zmijewski Sebagai Metode dalam Memprediksi Kondisi Kebangkrutan pada PT. Garuda Indonesia, Tbk Periode 2014-2018 - Desyah Natalia Bilondatu; Meriyana Franssisca Dungga; Selvi Selvi (STIE Kertanegara Malang, 2019)
This study aims to find out, describe and explain the results of the application of analysis from the prediction method of bankruptcy of the Altman Z-Score, Springate, and Zmijewski models used in assessing and predicting the potential for bankruptcy with the object of research at PT. Garuda Indonesia (Persero) Tbk 2014-2018. The method used in this research is descriptive research method using a quantitative approach, and the operationalization of the variables used is the independent variable, namely the bankruptcy prediction model with the dependent variable is financial ratios. The data used are secondary data in the form of annual financial reports (annual reports) PT. Garuda Indonesia (Persero) Tbk for the period 2014 to 2018. The results of this study indicate that the Altman Z-Score, Springate and Zmijewski methods are able to measure and predict bankruptcy of companies with different portions according to the calculations applied in each of these analyzes.Keywords: Altman Z-Score, Springate, Zmijewski, and Bankruptcy